PSIKOLOGI KOGNITIF MEMAKNAI HIDUP MELALUI NIKMAT - Ika Aulia (Program Studi Psikologi Islam, 2023)
Cognitive Psychology is an alternative in helping a person's mental processes that underlie the ability to perceive the world, understand and remember experiences, communicate with others, and control behavior. This flow places humans as creatures who actively react to their environment by thinking and studying how the flow of information is captured by the senses which are processed in a person's soul before being manifested in the form of behavior. This research uses literature study method. Research using the literature study method is included in descriptive research that focuses on facts obtained in a systematic way that originates from journals, books, and papers. The thought process is a blessing. From that pleasure, we can feel something that arises from within us or responds to something that is seen or heard. So from that pleasure or taste, we can know something that is true and false.